Physics-basis simulation of bubble pinch-off - Kei ITO (The Japan Society of Mechanical Engineers, 2016)
In the last two decades, CFD codes have been widely used for the design studies of NPPs. Recently high-precision simulation models have been developed to evaluate complicated phenomena, e.g. fuel melting in severe accident. The authors also are developing a high-precision CFD code with an interface tracking method to simulate the gas entrainment (GE) phenomena in sodium-cooled fast reactors (SFRs), which might be caused by a highly-intensified free surface vortex. The GE in SFRs is characterized by an elongated interfacial dent along the vortex core and the bubble pinch-off at the tip of the dent. To simulate this complicated phenomenon, the authors’ CFD code has physics-basis algorithms which model accurately the interfacial dynamic behavior, the pressure jump condition at an interface and the surface tension. Several verification problems, e.g. the slotted-disk problem, have been already solved and the accuracy of each individual algorithm is confirmed. In this paper, a basic experiment of the GE is simulated to validate the developed CFD code. In the experiment, the entrained gas flow rate is measured by image processing with a high-speed video camera. The simulation result of the entrained flow rate shows comparable value to the experimental data, that is, our CFD code is considered applicable to the evaluation of the GE in SFRs.